MODEL FOR TRAINING ENGINEERING DESIGN STUDENTS BY USING METHODS FROM HUMANITIES AND SOCIAL SCIENCES - Vodenova, Pavlina; Kaneva, Ophelia (Innovation in Woodworking Industry and Engineering design, 2021)
This article presents a successful model of training practice as part of the student’s education in "Engineering Design" (Interior and Furniture Design) Program at the University of Forestry. Stimulation and emphasizing the strengths of the learners by provoking a new teaching style for the traditional training of designers and engineers is the main accent of this model. The model itself is not just conceptual, but also applied in the training of students in design programs and could be also successfully implemented in a wide range of cross-disciplinary platforms in the training of designers and engineers (and not only). At the same time, this innovative approach highlights new forms of support for students' learning progress, expanding the operationalization of their involvement in direct work with clients with diverse status and needs.